Heterotopic Gastric Mucosa Presenting as Lower Gastrointestinal Bleeding: An Unusual Case Report - Syed Muhammad Ali; Ayman Abdelhafiz Ahmed; Leena Amin Hussain Saaid; Gihan Mustafa Kamal Mohamed; Amjad Ali Shah; Mohannad Al-Tarakji; Zia Aftab; Inamulla; Sameera Rashid (Case Reports in Surgery)
Heterotopic gastric mucosa (HGM) is gastric mucosal tissue outside the stomach. It can be discovered anywhere throughout the gastrointestinal tract and is mostly asymptomatic. HGM, although rare beyond the ligament of Treitz, should be included in the differential diagnosis in a young patient with a polyp causing obstructive symptoms or bleeding. Very few cases are published in literature. We describe a case of young male who presented with an episode of large amount of melena, from a bleeding jejunal lesion, diagnosed by endoscopy. Laparotomy and wedge resection of the jejunal lesion was done, and histopathology showed gastric heterotopia in a small jejunal diverticulum.